Additive Manufacturing (AM) of Metallic Alloys - Calignano, Flaviana (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The introduction of metal AM processes in such industrial sectors as the aerospace, automotive, defense, jewelry, medical and tool-making fields, has led to a significant reduction in waste material and in the lead times of the components, innovative designs with higher strength, lower weight, and fewer potential failure points from joining features. This Special Issue on "Additive Manufacturing (AM) of Metallic Alloys" contains a mixture of review articles and original contributions on some problems that limit the wider uptake and exploitation of metals in AM.